Repeatability and agreement of swept-source optical coherence tomography and partial coherence interferometry biometers in myopes - Garcia Ardoy, Elisa (2023)
Background: The Myopia Master is a new biometer based on partial coherence interferometry especially dedicated to the follow-up of myopic patients. This study aims to assess the repeatability of the Myopia Master and evaluate its agreement with a swept-source optical coherence interferometry biometer (IOL Master 700).MethodsThis cross-sectional prospective study assessed the biometric parameters of two groups of myopes (age range: 8-16 years old), spectacle corrected (n = 60) and orthokeratology contact lens wearers (n = 60). One senior optometrist performed two consecutive measurements per instrument, which included axial length, mean keratometry and horizontal visible iris diameter (HVID). The repeatability of each device and the agreement between devices were assessed by the dispersion of the measurement differences, for AL, mean keratometry, corneal astigmatism and HVID.ResultsThe two biometers measured approximately the same value in both measurements. Test-retest repeatability tended to be lower than clinical significant thresholds, in particular, for AL and mean keratometry. Corneal-related parameters tended to have lower repeatability in the orthokeratology group, especially mean keratometry. The agreement between instruments revealed statistically significant differences between devices with the SS-OCT measuring longer eyes, steeper corneas and larger HVID.ConclusionsIn a paediatric population, the Myopia Master showed clinically acceptable repeatability levels, but the IOL Master 700 demonstrated superior repeatability. Eyes treated with orthokeratology may compromise the repeatability of the corneal-related parameters. The Myopia Master and the IOL Master 700 are repeatable devices appropriate for monitoring myopia progression, but the differences observed do not allow their use interchangeably.